Nutritive value of rapeseed meals and cakes for pigs and sheep - Salo, Maija-Liisa (Agricultural and Food Science, 1982)
Digestibility and nutritive value for growing pigs, liveweight 40-70 kg, were determined for high glucosinolate (HG) Span and Torch (Brassica campestris) rapeseed meals (RSM) and cakes (RSC), and for low glucosinolate (LG)Regent (B. napus) RSM and DF-15 (B. campestris) RSC in barley based diets in one year or two successive years. Some of the feeds were evaluated also for sheep. The level of RSM and RSC was 20 or 30 % of diets for pigs and 32 % for sheep. The observed net energy value of commercial Span-Torch RSM for pigs was in two successive years 0.80 and 0,79 f.u./kg dry matter (DM) ( f.u. = feed unit = 0.7kg starch equivalent).The protein values were 281 and 291 g digestible crude protein (DCP)/kg DM, respectively. The 8 %-units higher fat content together with a little better digestibility of organic components raised the f.u. value of RSC about 30 % above that of RSM. For pigs there were only slight differences in the digestibility and palatability of the HG Span-Torch and the LG Regent and DF-15 meals and cakes, but there was a clear difference in the palatability in successive years. The nitrogen balances for pigs on the RSM or RSC and barley diets were 20.4-22.2 g N/d, and the biological values of protein of the RSM and RSC were 67-68. The net energy value of Span-Torch rapeseed meal for sheep was 0.91 f.u./kg DM, and the protein value 309 g DCP/kg DM. The digestibility of cakes was nearly equal to meal, but the 8 %-units higher fat content raised the f.u. value of RSC about 20 %. The digestibility of organic matter of LG DF-15 cakes was a little better (P < 0.05) than that of Span-Torch cakes. The sheep willingly ate RSM and RSC at a 32 % level of the diets.